Study of Knowledge, History of Allergies, and Personal Hygiene on the Incidence of Dermatitis - Marniati Marniati; Sufyan Anwar; Teuku Muliadi; Itza Mulyani; Muhammad Iqbal Fahlevi (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
A Knowledge factor, allergy history, and environment strongly influence the incidence of Dermatitis, followed by allergy history factors. From the survey results, the problem in this study is the high cases of Dermatitis in the community, which reached 623 points. This study aims to examine the impact of Knowledge, history of allergies, and the environment on the incidence of Dermatitis in the working area of Alue Rambot health center, Darul Makmur District Nagan Raya district. The research method used in this research is analytic with a cross-sectional design. This research was conducted in January 2022, The population in this study is people who suffer from Dermatitis in the working area of the Alue Rambot Health Center, as many as 623 sufferers, the sample in this study was taken based on the Slovin formula with an error rate (0.1), where a sample of 86 respondents was obtained with criteria who were willing to be interviewed and were in the working area of the Puskesmas.  Processing data using statistical tests, namely univariate and bivariate analysis, then tested using the Chi-Square test. The study results stated that after being analyzed, it turned out that there was an impact of Knowledge, history of allergies, and the environment affected the incidence of Dermatitis as evidenced by the value (P-value 0.05) with the Prevalence Ratio (7.302, 3.062, and 2.460). The conclusion turns out that the lack of public knowledge about the causes of Dermatitis, the presence of a previous history of allergies, and the environment regarding poor personal Hygiene has a significant influence on the incidence of Dermatitis. Local government advice directly implement socialization about Dermatitis by increasing Knowledge, breaking the chain of causes of allergy recurrence, and improving the cleanliness of the surrounding environment for the formation of work areas whose communities are dermatitis-free.